Review on the potential co-application of aqueous CO2 solution in cementitious material - Zulhaziq Khan Zuljar; Warid Wazien Ahmad Zailani; Nazirah Mohd Apandi; Khanom Simarani; Norlia Mohamad Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2024)
The escalating concerns over climate change and the urgent demand for sustainable development have propelled significant efforts to mitigate carbon footprints by sequestering carbon dioxide (CO2) into cementitious materials. One promising approach involves the incorporation of calcium-rich materials along with super-saturated aqueous solutions in cement, a method demonstrated to be effective in various studies. However, further research is necessary to address technical challenges and optimize the process. This paper presents a comprehensive review of the existing knowledge on the impact of different calcium-rich materials and curing conditions on the workability and compressive strength of concrete, with a particular focus on aqueous CO2. Utilizing the Systematic Literature Review (SLR) method, this study identifies the problem, selects the subject of investigation, and gathers pertinent information from suitable databases. The selected documents were analyzed, evaluated, and synthesized to combine the findings. Additionally, the parameters of carbonated concrete utilized in recent studies were analyzed and discussed, providing a thorough understanding of the current advancements and areas requiring further investigation.